Investment projects in logistics systems - Yuliya Prykhno (Розвиток методів управління та господарювання на транспорті, 2020)
Scientists have researched and scientifically substantiated the significant effect of the use of project management tools on all business entities and on the country's economy as a whole. At the same time, in modern conditions active economic development and turbulence environment, lead to the fact that considerable attention should be given to the strategic line of conduct of enterprises. The strategy allows to take into account the capabilities of the enterprise, as well as investment projects in various strategic business areas. Despite the fact that many sources describe the process of the development of logistics systems through investment projects; in practice it is very difficult to implement. For the implementation of investment projects of the enterprise it is necessary to present this process in the form of a set of formalized procedures or in the form of step-by-step sequence of actions for choosing the best option for an investment project.